2D Transistors: Vertical Integration of 2D Building Blocks for All‐2D Electronics (Adv. Electron. Mater. 12/2020). (9th December 2020) - Tang, Jian; Wang, Qinqin; Wei, Zheng; Shen, Cheng; Lu, Xiaobo; Wang, Shuopei; Zhao, Yanchong; Liu, Jieying; Li, Na; Chu, Yanbang; Tian, Jinpeng; Wu, Fanfan; et al.
Abstract : In article number 2000550, Guangyu Zhang and co‐workers realized vertically integrated multilayer all‐2D transistors based on gate‐all‐around structure and multilayer functional devices with excellent and comprehensive device performance. These devices demonstrate great potential for use in the next generation of sensing–processing–computing nanosystems and advanced electronic applications.